GRAY-BREASTED MOUNTAIN-TOUCAN Andigena hypoglauca, FIRST NEST RECORD - Vogt, Charles A.; Bravo, Xavier; Molina, Paul (Revista Ecuatoriana de Ornitología, 2024)
The first nest of Gray-breasted Mountain-Toucan Andigena hypoglauca is described, alongside observation on its nesting behavior and feeding. The nest was observed in Llaviucu, province of Azuay, southern Ecuador.